Yukon-Charley Rivers National Preserve, Alaska : general management plan, environmental assessment, land protection plan, Charley wild river management plan, wilderness suitability review. - United States. National Park Service. ([Denver, Colo.] : Denver Service Center, U.S. Dept. of the Interior, National Park Service : U.S. G.P.O., 1983)
"September 1983." Cover title. Mode of access: Internet.